Ancestral Beliefs, Religious Systems and Views of Life Traditional Dayak Community - Kwirinus, Dismas; Saeng, Valentinus (Universitas Muhammadiyah Surakarta, 2023)
This research focuses on the traditional Dayak belief systems, including their views on ancestor worship, religious systems, and worldviews. The Dayak's understanding of their belief system stems from imagination and attempts to relate their experiences to a greater power that governs the universe. The important thing about ancestral beliefs and this religious system is that nature does not exist on its own but that something has created it. They call this power Tamai Tingai, which is the center of their religious experience. Religious life is a theophanic experience that influences all Dayak human life. This paper aims to describe and analyze the concept of ancestral beliefs and religious systems as a way of life for the traditional Dayak community. This study uses phenomenological analysis and critical reading of the text using qualitative research methods. The research findings show that the Dayak people realize that religious expression through ancestor worship and religious systems is justified by human experience. In situations of helplessness, humans seek help and find it by connecting themselves to a transcendent existence.